On almost precontinuous functions - Saeid Jafari; Takashi Noiri (International Journal of Mathematics and Mathematical Sciences)
Nasef and Noiri (1997) introduced and investigated the class of almost precontinuous functions. In this paper, we further investigate some properties of these functions.